2003
DOI: 10.1096/fj.02-0456fje
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine‐betaine interactions in a murine model of 5,10‐methylenetetrahydrofolate reductase deficiency

Abstract: Hyperhomocysteinemia, a proposed risk factor for cardiovascular disease, is also observed in other common disorders. The most frequent genetic cause of hyperhomocysteinemia is a mutated methylenetetrahydrofolate reductase (MTHFR), predominantly when folate status is impaired. MTHFR synthesizes a major methyl donor for homocysteine remethylation to methionine. We administered the alternate choline-derived methyl donor, betaine, to wild-type mice and to littermates with mild or severe hyperhomocysteinemia due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
125
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(141 citation statements)
references
References 49 publications
12
125
2
2
Order By: Relevance
“…Because smoking is known to be associated with compromised folate status, this suggests an increased importance of alternative methyl group donors under folate deficient conditions, which for example has been shown for betaine (42,43) and may also apply to methionine and choline. In addition, smoking has been associated with lower circulating concentrations of vitamin B2 and B6 (44).…”
Section: Smoking As Potential Effect Modifiermentioning
confidence: 99%
“…Because smoking is known to be associated with compromised folate status, this suggests an increased importance of alternative methyl group donors under folate deficient conditions, which for example has been shown for betaine (42,43) and may also apply to methionine and choline. In addition, smoking has been associated with lower circulating concentrations of vitamin B2 and B6 (44).…”
Section: Smoking As Potential Effect Modifiermentioning
confidence: 99%
“…While BHMT, unlike MTRR, is not directly involved in the folate-dependent pathway, experiments have shown that homocysteine flux through the BHMT pathway is enhanced when folate-dependent remethylation is disrupted [22]. Betaine can effectively lower plasma homocysteine levels and there is a significant negative correlation between plasma homocysteine and plasma betaine, as shown in men with coronary artery disease [22]. Thus, BHMT may play a critical role in the remethylation of homocysteine when the folate-dependent pathway is compromised by either genetic or dietary factors.…”
mentioning
confidence: 99%
“…Les taux d'homocystéine plasmatique totale de ces souris hétérozygotes et homozygotes sont respectivement 1, 6 et 10 fois supé-rieurs à ceux des témoins [25]. Ces souris présentent une stéatose hépatique qui pourrait être reliée à la diminution des taux de métabolites de la choline dans le foie [26]. Ces souris ont servi à tester l'effet de la bétaïne dans les cas de déficience en MTHFR [26].…”
Section: Modèle Animalunclassified
“…Ces souris présentent une stéatose hépatique qui pourrait être reliée à la diminution des taux de métabolites de la choline dans le foie [26]. Ces souris ont servi à tester l'effet de la bétaïne dans les cas de déficience en MTHFR [26]. [27].…”
Section: Modèle Animalunclassified